Iconoclasm as child's play - Moshenska, Joe, 1983- (Stanford University Press, 2019)
Taking its impetus from remarkable fact that holy things were given to children as toys in the early modern period as a way of destroying their power, this book rethinks the meaning of both iconoclasm and child's play then and now.